2008
DOI: 10.1007/s00404-008-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida sp. in the cervical–vaginal cytology stained by Harris–Shorr

Abstract: With the results obtained, it was noticed that the socio-economical level does not seem to influence the epidemiology of the Candida sp. and pointed to a balance in terms of numbers of this agent in Maringá, Paraná, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
2
9
0
1
Order By: Relevance
“…As per the investigation of Jamilian et al [6] , C. albicans was confined in 42.03% of VVC patients, while in the rest of the cases, the sickness was caused by other Candida species. This example of progress was likewise noted in different nations [2,5,9] . Ahmad et al [9] detailed a pervasiveness of 53.1% of non-albicans species among patients with VVC, where C. glabrata (36.7%) was the most well-known secluded species.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…As per the investigation of Jamilian et al [6] , C. albicans was confined in 42.03% of VVC patients, while in the rest of the cases, the sickness was caused by other Candida species. This example of progress was likewise noted in different nations [2,5,9] . Ahmad et al [9] detailed a pervasiveness of 53.1% of non-albicans species among patients with VVC, where C. glabrata (36.7%) was the most well-known secluded species.…”
Section: Introductionsupporting
confidence: 60%
“…Vulvovaginal Candidiasis (VVC), as an imperative subtype, is portrayed by extreme tingling of vulva, anomalous vaginal release, erythema, edema of vulva, and satellite injuries [1] . Numerous examinations have appeared 75% of the female populace will have somewhere around one scene of VVC and 40 -half will have intermittent episodes, amid their lifetime [2,4] . In spite of a few treatment modalities and use of new successful medications, VVC is an intricate and extensive issue in gynecology and obstetrics [4] .…”
Section: Introductionmentioning
confidence: 99%
“…5 75% of the sexually active women have been found to have symptomatic vaginal candidiasis at least once in their life and 40-50% will have recurrent episodes during their lifetime. [6][7][8][9] In spite of several treatment modalities and application of new effective drugs, VVC is a complex and considerable problem in gynecology and obstetrics. 10 In present study, Candida species was isolated in 42 cases (22.8%), out of the total 184 women.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly thought that the environment of BV is not conducive to blastospore multiplication, and that fungal infection therefore does not occur in the presence of BV [6]. Souza et al [7] noted that the most common bacterial flora associated with 3,125 instances of Candida spp. was of lactobacilli, present in 73.63% of the instances, followed by mixed flora (25.40%) and BV (0.73%).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between Candida albicans and BV remains controversial [5,6,7,8,9,10,11,12]. It is generally thought that coexisting C. albicans and BV are rare [5]; the reasoning behind this is that the growth requirements of the two are completely opposite to each other [6], but a recent study has indicated that this view is incorrect [10].…”
Section: Introductionmentioning
confidence: 99%